(untitled) (Marketing Journal, 2025)
In this article, enterprises can improve their position in the market compared to competitors, reduce costs, increase efficiency, enhance consumer satisfaction, identify weak points, determine the strategic goal of the enterprise in the market, identify information sources, determine the type and volume of information, choose information collection methods, analyze inform ation, and review the content and technology of benchmarking.